In Vitro Pathogenicity of Bacterial Brown Band Disease on Acropora sp. (April 2019) - Rahmi,; Jompa, J; Tahir, A
Abstract: This study aimed to determine which bacteria trigger brown band disease (BrB) through assessing the level of pathogenicity of bacteria present and microscopic histological analysis of coral tissue cells. The study was conducted from October 2014 to March 2015. The bacterial culture stage was conducted at the Faculty of Medicine Microbiology Laboratory, Universitas Hasanuddin, the histological analysis was conducted at the, Maros Veterinary Centre Pathology Laboratory, and pathogenicity tests of bacteria from brown band disease on healthy corals were conducted at the Marine Station Hatchery of the Faculty of Marine Science and Fisheries, Universitas Hasanuddin, on Barrang Lompo Island. Pathogenicity tests indicated that post-infection time before the appearance of BrB symptoms was different for each bacteria tested. The fastest-acting bacterial strain was Acinetobacter sp. RA3849 ORF, which caused disease symptoms in 5 hours, followed by Streptococcus sp. YM395 (9 hours), E . faecalis C56 (20 hours), and Vibrio alginolyticus H2X5 (22 hours). Acinetobacter sp. also produced the highest rate of infection spread in Acropora sp., reaching 5.05 cm/day. Histological observation showed tissue damage (necrosis) due to bacterial infection in the epidermal layer and hyperplasia of the gastrodermal layer, where there was an abnormal increase in abnormal tissue or organs due to an increase in the number of cells. The in vitro pathogenicity test showed that Acinetobacter sp. strain RA3849 reacts as a trigger of BBD disease.